Study on emulsion stability and chemical demulsification characteristics - Ahmad Syauqi, Othman (2009)
Water in oil emulsion occurs at many stages in the production and treatment of crude oil. About two third of petroleum production of every oil field exists in the form of water in oil emulsion. The emulsion stability results from the presence of interfacial barrier preventing coalescence of the dispersed water droplets. This is due to the present of polar components such as asphaltenes, resins, wax and naphtenic acids in the crude oil. It has been reported that the combination of oil-soluble demulsifiers and water-soluble demulsifiers produced great result in water separation. From the screening process of single oil-soluble demulsifiers, the most effective chemicals as demulsifier are hexylamine and dioctylamine while butanoic acid, and formic acid are the most effective chemicals in water-soluble group. This new formulation was found to be effective for demulsification of water-in-oil emulsion of Dubai, Miri, and Masilah fields emulsion system. In order to obtain better understanding and results, optimizing on agitation and temperature conditions, the mechanism demulsification study are recommended for further study.